The Ideology of Socialism and the Armenian Political Parties - Hovhannisyan, Gegham (Տիգրան Մեծ)
The article covers the manifestations and peculiarities of the ideology of socialism in the social-political life of Armenia at the end of the 19th century and the beginning of the 20th century. General char-acteristics aims and directions of activity of the political organizations functioning in the Armenian reality within the given time period, whose program documents feature the ideology of socialism to one degree or another, are given (Hunchakian Party, Dashnaktsutyun, Armenian Social-democrats, Specifics, Socialists-revolutionaries). The specific peculiarities of the national-political life of Armenia in the given time period and their impact on the ideology of political forces are introduced.
Keywords: Political Philosophy